2020
DOI: 10.2298/jsc180302082m
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of novel phthalimido oxime pseudoesters and evaluation of their cytotoxicity

Abstract: A series of novel optically pure oxime pseudoesters derivatives were synthesized by the reaction of substitute keto oximes with various N-substituted α-amino acids chlorides in the presence of triethylamine and dichloromethane at 0 °C, and their structures were characterized by IR and 1D-NMR methods. The synthesized compounds were tested for their ability to inhibit the proliferation of human colon cancer cells and human epithelial cells. Some of them were revealed to have a significant cytotoxic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…64, No. 6 (2021) increase in reaction time [12,15,17,29]. Conducting the practice in an acetic acid environment makes the method relatively efficient and economical [30,31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…64, No. 6 (2021) increase in reaction time [12,15,17,29]. Conducting the practice in an acetic acid environment makes the method relatively efficient and economical [30,31].…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that they may be compounds with leading potential in the development of anti-obesity drugs [11]. It has also been found that pseudoesters of phthalimidooxims exhibit strong cytotoxic activity in human cancer cells [12]. When the neurotoxic and antiepileptic properties of compounds obtained by combining gamma amino butyric acid (GABA), phthalimide, hydrazone, and anilides with different pharmacophore properties into a single molecule were studied, most of the compounds showed activity in scSTY and ipPIC models [13].…”
Section: Introductionmentioning
confidence: 99%